Driving Change : The Story of the South Africa Norway Tertiary Education Development Programme - Gibbon, Trish (Book collections on Project MUSE., 2014)
Driving Change tells a story that exemplifies a basic law of physics, known to all ñ the application of a relatively small lever can shift weight, create movement and initiate change far in excess of its own size. It tells a story about a particular instance of development cooperation, relatively modest in scope and aim that has nonetheless achieved remarkable things and has been held up as an exemplar of its kind. It does not tell a story of flawless execution and perfectly achieved outcomes: it is instead a narrative that gives some insight into the structural and organisational arrangements.